Risk Factors for Severe Outcomes in Patients With Systemic Vasculitis and COVID‐19: A Binational, Registry‐Based Cohort Study. Issue 9 (27th July 2021) - Rutherford, Matthew A.; Scott, Jennifer; Karabayas, Maira; Antonelou, Marilina; Gopaluni, Seerapani; Gray, David; Barrett, Joe; Brix, Silke R.; Dhaun, Neeraj; McAdoo, Stephen P.; Smith, Rona M.; Geddes, Colin C.; et al.
Abstract : Objective: COVID‐19 is a novel infectious disease with a broad spectrum of clinical severity. Patients with systemic vasculitis have an increased risk of serious infections and may be at risk of severe outcomes following COVID‐19. We undertook this study to establish the risk factors for severe COVID‐19 outcomes in these patients, including the impact of immunosuppressive therapies. Methods: A multicenter cohort was developed through the participation of centers affiliated with national UK and Ireland vasculitis registries. Clinical characteristics and outcomes are described. Logistic regression was used to evaluate associations between potential risk factors and a severe COVID‐19 outcome, defined as a requirement for advanced oxygen therapy, a requirement for invasive ventilation, or death. Results: The cohort included 65 patients with systemic vasculitis who developed COVID‐19 (median age 70 years, 49% women), of whom 25 patients (38%) experienced a severe outcome. Most patients (55 of 65 [85%]) had antineutrophil cytoplasmic antibody–associated vasculitis (AAV). Almost all patients required hospitalization (59 of 65 [91%]), 7 patients (11%) were admitted to intensive care, and 18 patients (28%) died. Background glucocorticoid therapy was associated with severe outcomes (adjusted odds ratio [OR] 3.7 [95% confidence interval 1.1–14.9]; P = 0.047), as was comorbid respiratory disease (adjusted OR 7.5 [95% confidence interval 1.9–38.2]; P = 0.006). Vasculitis disease activity and nonglucocorticoid immunosuppressive therapy were not associated with severe outcomes. Conclusion: In patients with systemic vasculitis, glucocorticoid use at presentation and comorbid respiratory disease were associated with severe outcomes in COVID‐19. These data can inform clinical decision‐making relating to the risk of severe COVID‐19 in this vulnerable patient group.